Immigrants and Gender Roles: Assimilation vs. Culture - Francine D. Blau (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper examines evidence on the role of assimilation versus source country culture in influencing immigrant women's behavior in the United States—looking both over time with immigrants' residence in the United States and across immigrant generations. It focuses particularly on labor supply but, for the second generation, also examines fertility and education. Considerable evidence is found that immigrant source country gender roles influence immigrant and second generation women's behavior in the United States. At the same time, the results suggest considerable evidence of assimilation of immigrants.
Keywords: J13; J16; J22; J24; J61; 330; gender; immigration; labor supply; wages; social capital; culture; human capital